2018
DOI: 10.18632/oncotarget.24866
|View full text |Cite
|
Sign up to set email alerts
|

Single-walled and multi-walled carbon nanotubes induce sequence-specific epigenetic alterations in 16 HBE cells

Abstract: Recent studies have identified carbon nanotube (CNT)-induced epigenetic changes as one of the key players in patho-physiological response. In the present study, we investigated whether CNT exposure is associated with epigenetic changes in human bronchial epithelial cells (16 HBE), in vitro. We focused on global DNA methylation, methylation of LINE-1 elements and promoter sequence of twelve functionally important genes (SKI, DNMT1, HDAC4, NPAT, ATM, BCL2L11, MAP3K10, PIK3R2, MYO1C, TCF3, FGFR 1 and AGRN). Addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 78 publications
0
17
0
1
Order By: Relevance
“…No alteration of global DNA methylation was found [ 66 ]. An increased alteration on CpG sites after short -and long-term exposure has also been described for both benchmark short NM-400 MWCNTs and asbestos (CDKN1A and ATM among others) [ 66 , 67 , 68 , 69 , 70 ].…”
Section: Carbon Nanotubes and The Hallmarks Of Cancermentioning
confidence: 95%
“…No alteration of global DNA methylation was found [ 66 ]. An increased alteration on CpG sites after short -and long-term exposure has also been described for both benchmark short NM-400 MWCNTs and asbestos (CDKN1A and ATM among others) [ 66 , 67 , 68 , 69 , 70 ].…”
Section: Carbon Nanotubes and The Hallmarks Of Cancermentioning
confidence: 95%
“…Specifically, exposure to MWCNTs resulted in promoter hypomethylation of 2398 genes, whereas exposure to SWCNTs predominantly caused hypomethylation of individual CpG sites in 501 genes residing in the gene body and promoter regions, including the SKI , GSTP1 , SHROOM2 , and NF1 genes. Significant changes in gene-specific DNA methylation were reported in another study after 24 h of exposure of 16HBE14 bronchial epithelial cells to SWCNTs and MWCNTs [ 18 ]. At least one CpG site was differentially methylated (while some of the CpG sites were hypomethylated, others were hypermethylated, often within the same gene promoter region) in DNMT1 and MYO1C after exposure to SWCNTs, in HDAC4 and MAP3K10 after exposure to MWCNTs, and in NPAT/ATM and PIK3R2 after exposure to both MWCNTs and SWCNTs.…”
Section: Dna Methylation Alterations Induced By Exposure To Nanomatermentioning
confidence: 99%
“…At least one CpG site was differentially methylated (while some of the CpG sites were hypomethylated, others were hypermethylated, often within the same gene promoter region) in DNMT1 and MYO1C after exposure to SWCNTs, in HDAC4 and MAP3K10 after exposure to MWCNTs, and in NPAT/ATM and PIK3R2 after exposure to both MWCNTs and SWCNTs. In contrast to alterations in gene-specific DNA methylation, no changes in the level of global cytosine DNA methylation were found in SWCNTs- and MWCNTs-exposed cells [ 16 , 18 ]. However, in a study by Emerce et al [ 19 ] the authors demonstrated a significant loss of global DNA methylation in 16HBE14 cells exposed to MWCNTs.…”
Section: Dna Methylation Alterations Induced By Exposure To Nanomatermentioning
confidence: 99%
“…The carbon nanotubes used for the present study are reference materials, which have been widely used in our previous studies 46,62,63 and in projects like the NANOGENOTOX. SWCNTs were purchased from US National Institute of Standards and Technology (NIST-SRM2483) and MWCNTs were purchased from the European Commission Joint Research Centre (JRC-NM400).…”
Section: Test Substancesmentioning
confidence: 99%